Estimación del índice de merito total del programa de mejoramiento genético sostenible de bovinos de leche de la parroquia Joseguango Bajo. - Baquero Díaz, Paula Sofia (2023)
The present investigation was carried out at Cotopaxi province, Latacunga canton Joseguango Bajo parish, 28 producers were part of the study who have 168 animals. The following was performed, such as records of production costs, deworming, multivitamins, live weight intake, milk weight intake, density and mastitis test through California Mastitis Test (CMT), in addition to gynecological check-ups, artificial inseminations and fixed-time artificial inseminations specifically with calves, cows, pregnant cows, cows in production, calves and bullocks. Based on cost production were $0.19 is the benefit production a liter of milk, which is marketed at $0.42, 80% from these expenses represent the purchase of green plantain rejection, for which monthly benefit of producers is $243, so, in the parish 3 important objectives were set: daily weight gain is 400 g/day and it is estimated to reach 700 g/day in 2 generations, like an average of liters produced monthly with 909 liters and density with an average that oscillates between 1,017 gr/ml to 1,029 gr/ml. Finally, in relation to the 3 objectives, 7 animals were selected, which complied with the established parameters, as well as an up-to-date health calendar and all the exposed characteristics, so that in the future their genetic material can be transmitted on farms a the parish.